RuO2 Thin Films Electrodeposited on Polystyrene Nanosphere Arrays Growth Mechanism and Application to Supercapacitor Electrodes - Hong, Dajung (Langmuir : the ACS journal of surfaces and colloids, 2018)
Two-dimensionally (2D) arrayed polystyrene (PS)/ruthenium oxide (RuO2) core/shell nanospheres are successfully prepared by the electrodeposition of RuO2 nanoparticles on a hexagonal close-packed PS monolayer. This nanosphere structure is entirely different from the structure previously reported for other transition metal oxides electrodeposited on the PS nanosphere arrays. The different growth behavior is analyzed, and a possible deposition mechanism is proposed based on the morphological evolution and photoelectron spectroscopy measurements. As an electrode for supercapacitors, this 2D arrayed nanosphere structure exhibits superior capacitive properties such as significantly large areal capacitance, tight binding with current collectors, and retarded saturation of the capacitance, compared to a planar RuO2 film electrode